Inspiratory Muscle Training for Obstructive Sleep Apnea: Protocol Development and Feasibility of Home Practice by Sedentary Adults - Krause-Sorio, Beatrix; An, Eunjoo; Aguila, Andrea P.; Martinez, Fernando; Aysola, Ravi S.; Macey, Paul M. (Frontiers in Physiology, 2021)
Background: Inspiratory muscle training (IMT) may improve respiratory and cardiovascular functions in obstructive sleep apnea (OSA) and is a potential alternative or adjunct treatment to continuous positive airway pressure (CPAP). IMT protocols were originally designed for athletes, however, we found some OSA patients could not perform the exercise, so we aimed for a more OSA friendly protocol. Our feasibility criteria included 1) participants successfully managing the technique at home; 2) participants completing daily practice sessions and recording data logs; and 3) capturing performance plateaus to determine an optimal length of the intervention. Methods: Five sedentary OSA patients participated in this feasibility study (3 men, mean age=61.6 years, SD=10.2). Using a digital POWERbreathe K4 or K5 device, participants performed 30 daily inhalations against a resistance set at a percentage of maximum, recalculated weekly. Participants were willing to perform one but not two daily practice sessions. Intervention parameters from common IMT protocols were adapted according to ability and subjective feedback. Some were unable to perform the typically used 75% of maximum inspiratory resistance so we lowered the target to 65%. The technique required some practice; therefore, we introduced an practice week with a 50% target. After an initial eight weeks, the intervention was open-ended and training continued until all participants demonstrated at least one plateau of inspiratory strength (2 weeks without gain). Weekly email and phone reminders ensured that participants completed all daily sessions and logged data in online surveys. Weekly measures of inspiratory resistance, strength, volume, and flow were recorded. Results: Participants successfully completed the practice and subsequent 65% IMT resistance targets daily for 13 weeks. Inspiratory strength gains showed plateaus in all participants by the end of 10 weeks, suggesting 12 weeks plus practice would be sufficient to achieve and capture maximum gains. Participants reported no adverse effects. Conclusion: We developed and tested a 13-week IMT protocol in a small group of sedentary, untreated OSA patients. Relative to other IMT protocols, we successfully implemented reduced performance requirements, a practice week, and an extended timeframe. This feasibility study provides the basis for a protocol for clinical trials on IMT in OSA.